Analysis Of Factors Affecting Job Satisfaction Of State Civil Servants At The Regional Financial Agency Of Kaur Regency - Hodiah Apriani; Ida Anggriani; Yanto Effendi (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2021)
The purpose of this study is to determine the factors that affect job satisfaction of State Civil Servants at the Regional Finance Agency of Kaur Regency. Results of the study showed that the results of the t test were the need fulfillment variable (X1), the discrepancies variable (X2), the value attainment variable (X3), the equity variable (X4), the genetic component variable, component (X5) partially does not have a significant effect on job satisfaction of state civil servants (Y) at the Regional Finance Agency of Kaur Regency. results of the F simultaneously or together have a significant effect on job satisfaction of state civil servants.